Konservasi Tanah dan Air melalui Penerapan Lubang Resapan Biopori (LRB) di Desa Aik Prapa, Lombok Timur - Arben Virgota; Baiq Farista; Suripto; Lalu Adi Gunawan; Rachmawati Noviana Rahayu; Nur Indah Julisaniah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Socialization and training regarding Biopori Infiltration Holes (LRB) need to be carried out to overcome the problem of limited water availability in Aik Prapa Village. LRB allows rainwater that is absorbed into the ground to be stored in groundwater reserves. This stored groundwater can be used for plant water needs and other water needs. This community service activity aims to increase community knowledge and skills regarding LRB application techniques in efforts to conserve soil and water resources. The socialization method used is in the form of counseling and distribution of leaflets (brochures). The practice of making LRB is carried out independently by the participants and is still accompanied by the Service Team. The targets of this activity were youth groups, several farmer groups and PKK members of Aik Prapa Village. The success of this activity was demonstrated by the enthusiasm of the participants during the activity, the ability of the participants to make LRB, and the willingness of the participants to implement LRB in their plantations. or their home environment. Monitoring results show that the community has implemented 11 biopore infiltration holes. The application of biopore infiltration holes is expected to be the start of an environmental improvement process in Aik Prapa Village so that in the future limited water availability will no longer be a problem.